Management of Persistent Hyponatremia after Off-Pump Coronary Artery Bypass Grafting: A Case Report - Bibifatemeh Shakhsemampour; Faegheh Zojaji; Ahmad Amouzeshi (Golestan University Of Medical Sciences, 2019)
Background: Delayed hyponatremia is a common phenomenon following transsphenoidal surgery. Recent evidence suggests that the risk of developing intensive care unit-acquired hyponatremia is high following cardiac surgery. Herein, we report management of persistent hyponatremia after off-pump coronary artery bypass in a patient with diabetes and hypothyroidism who was on diuretics. Case description: An 81-year-old man with diabetes and hypothyroidism was admitted to Valiasr hospital in Birjand (Iran) with history of typical chest pain and dyspnea since a month ago. Coronary angiography revealed a critical triple vessel disease, and therefore, the patient was considered a candidate for coronary artery bypass grafting. His pre-operative sodium level was normal but decreased to 128mEq/L on sixth postoperative day. Conclusion: When hyponatremia is detected in a patient with hypothyroidism, even if severe, in the absence of myxedema coma, it may not be directly associated with the lack of thyroid hormones. Thus, other possible etiologies should be considered.